2018
DOI: 10.1007/s11356-018-2454-8
|View full text |Cite
|
Sign up to set email alerts
|

Humic substances in Fluvisols of the Lower Vistula floodplain, North Poland

Abstract: The present study describes properties of humic substances of the Fluvisols (the Lower Vistula, Poland). Fluvisols under agricultural management (arable soil and grassland) were sampled from the surface horizon 50, 200, 600, and 900 m from the Vistula River. The content of carbon in the fractions of humic acids (C), fulvic acids (C), and humins (C) as well as the content of dissolved organic carbon (DOC) were assayed. The organic matter of the soils that were sampled 200 m from the river demonstrated a lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
7
4
0
Order By: Relevance
“…With the analysis of variance, it was found that the values of the parameters depended on the depth; the HAs molecules of the soils collected at depths of 10-20 cm and 20-30 cm demonstrated higher values of the ratio of HIL/ΣHOB than the HAs molecules of soils collected at a depth of 0-10 cm (p = 0.011 and p = 0.ditch. Similar dependencies were reported by Banach-Szott et al [90] for the humic acids of the Fluvisols sampled in the floodplains of the Vistula River; the values of the ratio HIL/ΣHOB were increasing with the distance from the riverbed. Interestingly, the values of that parameter recorded by Banach-Szott et al [90] were slightly higher, ranging from 0.72 to 0.81.…”
Section: Hydrophilic and Hydrophobic Nature Of Humic Acidssupporting
confidence: 87%
See 1 more Smart Citation
“…With the analysis of variance, it was found that the values of the parameters depended on the depth; the HAs molecules of the soils collected at depths of 10-20 cm and 20-30 cm demonstrated higher values of the ratio of HIL/ΣHOB than the HAs molecules of soils collected at a depth of 0-10 cm (p = 0.011 and p = 0.ditch. Similar dependencies were reported by Banach-Szott et al [90] for the humic acids of the Fluvisols sampled in the floodplains of the Vistula River; the values of the ratio HIL/ΣHOB were increasing with the distance from the riverbed. Interestingly, the values of that parameter recorded by Banach-Szott et al [90] were slightly higher, ranging from 0.72 to 0.81.…”
Section: Hydrophilic and Hydrophobic Nature Of Humic Acidssupporting
confidence: 87%
“…Similar dependencies were reported by Banach-Szott et al [90] for the humic acids of the Fluvisols sampled in the floodplains of the Vistula River; the values of the ratio HIL/ΣHOB were increasing with the distance from the riverbed. Interestingly, the values of that parameter recorded by Banach-Szott et al [90] were slightly higher, ranging from 0.72 to 0.81. Thus, the HAs molecules were identified with a slightly lower degree of maturity than the humic acids of Fluvisols.…”
Section: Hydrophilic and Hydrophobic Nature Of Humic Acidssupporting
confidence: 87%
“…The obtained results concerning the physico-chemical properties of the examined Fluvisols are comparable to the data obtained by other researchers. Similar results for total nitrogen and organic carbon content in Fluvisols from the river valley were also obtained by Banach-Szott et al [15]. However, these researchers obtained different pH values for soils depending on their distance from the riverbed.…”
Section: Soil Physicochemical Propertiessupporting
confidence: 85%
“…However, in general, the humic acids of the soils sampled 25 m away from the watercourse identified a higher degree of humification (the highest values of the ratio HIL/ΣHOB), as compared with the humic acids of the soils sampled 5 m away from the irrigation ditch. Similar dependencies were reported by Banach-Szott et al 62 for the humic acids of the Fluvisols sampled in the floodplains of the Vistula River; the values of the ratio HIL/ΣHOB were increasing with the distance from the riverbed. Interestingly, the values of that parameter recorded by Banach-Szott et al 62 were slightly higher, ranging from 0.72 to 0.81.…”
Section: Hydrophilic and Hydrophobic Nature Of Humic Acidssupporting
confidence: 87%
“…Similar dependencies were reported by Banach-Szott et al 62 for the humic acids of the Fluvisols sampled in the floodplains of the Vistula River; the values of the ratio HIL/ΣHOB were increasing with the distance from the riverbed. Interestingly, the values of that parameter recorded by Banach-Szott et al 62 were slightly higher, ranging from 0.72 to 0.81. Thus, the HAs molecules were identified with a slightly lower degree of maturity than the humic acids of Fluvisols.…”
Section: Hydrophilic and Hydrophobic Nature Of Humic Acidssupporting
confidence: 87%